Corp și cuvânt. Echilibru între instrumentele verbale și nonverbale - Mihăilă, Cătălina-Elena (Theatrical Research, 2023)
Body and Word. Balance Between Verbal and Nonverbal Instruments Starting from the written word, we can discuss a word spoken by the actor on stage that goes beyond the level of perfected sound and ends up being emitted with an inner meaning. Thus, the viewer enjoys a soundscape enriched by meaning. What happens, however, when nonverbal elements do not validate this word? How do we explain and solve unintended communication in order to reach effective communication?